Successful Early Rescue with Isatuximab Plus Carfilzomib-Dexamethasone (ISA-KD) in Daratumumab-Refractory Newly Diagnosed Multiple Myeloma (NDMM) Patients with “No Washout Period”: A Real-World Clinical Experience in A Case Series and Literature Review - Herreros, Paula Gili; Ramírez, Patricia García; Ocáriz, Xabier Gutiérrez López de; Charavía, Marta Callejas; García-Suárez, Julio; Gil-Fernández, Juan José (Archives of Clinical and Medical Case Reports, 2026)
Introduction: Anti-CD38 monoclonal antibodies, such as daratumumab and isatuximab, are key agents in multiple myeloma treatment. However, sequential use without a washout period remains controversial due to resistance concerns. Methods: We conducted a retrospective, real-world study of five newly diagnosed multiple myeloma (NDMM) patient’s refractory to daratumumab-based induction. Between June 2022 and December 2024, patients from two Spanish centers received isatuximab-carfilzomibdexamethasone (ISA-KD) immediately after daratumumab failure. Results: All patients achieved rapid, deep responses, enabling autologous stem cell transplantation in two cases. Conclusion: These findings suggest that immediate anti-CD38 switching